Relationship between Public Funding and Student Access: The Case of Two Public Universities in Africa (Higher Education Politics and Economics, 2025)
We examine changes in public funding and student access, and the role resource capacity plays in access to higher education by students in two public universities in Africa namely the University of the Western Cape, South Africa, and the University of Ghana, Ghana. The public funding of higher education and student access in South Africa and Ghana have changed over time, and various issues of concern have been raised about the changes.  The concerns raised border on the consistent decline in funding, especially public funding. With scarce resources, the governments cannot provide adequate financial support due to factors such as competing interests from other sectors of the economy. We discuss the nature of the changes in public funding and student access from 2007 to 2016. Data analysis is interpreted mainly through the lenses of resource dependence theory.